2022
DOI: 10.1111/tpj.15990
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis in Pinus revealed long‐term heat stress splicing memory

Abstract: SUMMARY Due to the current climate change, many studies have described main drivers in abiotic stress. Recent findings suggest that alternative splicing (AS) has a critical role in controlling plant responses to high temperature. AS is a mechanism that allows organisms to create an assortment of RNA transcripts and proteins using a single gene. However, the most important roles of AS in stress could not be rigorously addressed because research has been focused on model species, covering only a narrow phylogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…The use of a two-phase stress experimental design further confirmed the importance of sHSPs after initial heat stress and found changes in activated methyl cycle enzymes and H2A-H2B histone dimers associated with stress memory. Lamelas et al (2020b) also described changes in spliceosome-related proteins during heat stress and recovery, suggesting alternative splicing as an important mechanism mediating stress response and memory, which was further characterized by Roces et al (2022). Furthermore, the combined study of nuclear and chloroplast proteomes revealed the importance of proteins related to retrograde and anterograde signaling and to RNA metabolism rearrangement mediated by microRNAs, revealing a new layer of regulation in heat stress response (Lamelas et al, 2022).…”
Section: Pinus Sppmentioning
confidence: 95%
See 1 more Smart Citation
“…The use of a two-phase stress experimental design further confirmed the importance of sHSPs after initial heat stress and found changes in activated methyl cycle enzymes and H2A-H2B histone dimers associated with stress memory. Lamelas et al (2020b) also described changes in spliceosome-related proteins during heat stress and recovery, suggesting alternative splicing as an important mechanism mediating stress response and memory, which was further characterized by Roces et al (2022). Furthermore, the combined study of nuclear and chloroplast proteomes revealed the importance of proteins related to retrograde and anterograde signaling and to RNA metabolism rearrangement mediated by microRNAs, revealing a new layer of regulation in heat stress response (Lamelas et al, 2022).…”
Section: Pinus Sppmentioning
confidence: 95%
“… Lamelas et al. (2020b) also described changes in spliceosome-related proteins during heat stress and recovery, suggesting alternative splicing as an important mechanism mediating stress response and memory, which was further characterized by Roces et al. (2022) .…”
Section: Proteomics Survey (2012-2022): Where Are We Now?mentioning
confidence: 97%
“…Systems biology studies different layers of complexity of organisms in a high throughput manner, what we call omics, and then integrates them to obtain an accurate picture of an organism’s biology through its development or under different environmental conditions. Such an approach has been successfully applied in plant sciences to study, for example, the response to different types of stress in tree species [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ], Arabidopsis thaliana [ 8 , 9 ] or Chlamydomonas reinhardtii [ 10 , 11 ]. However, the integration of different omic levels is a rather challenging task.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, AS allows for increased flexibility during responses to changing environmental conditions ( Syed et al, 2012 ; Staiger and Brown, 2013 ; Filichkin et al, 2015 ). Several studies have contributed to our knowledge of crucial AS regulations upon HS ( Jiang et al, 2017 ; Ling et al, 2018 ; Sanyal et al, 2018 ; Vitoriano and Calixto, 2021 ; Roces et al, 2022 ). For example, we analysed rice response to HS and identified 2,162 differentially alternatively spliced (DAS) genes, many of which code for key regulators of gene expression, confirming that AS is a major part of the HS response ( Vitoriano and Calixto, 2021 ).…”
Section: Introductionmentioning
confidence: 99%